2020
DOI: 10.1016/j.medmal.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia susceptibility to ceftazidime-avibactam combination versus ceftazidime alone

Abstract: Background: Treatment options for Stenotrophomonas maltophilia (S. maltophilia) infections were limited. We assessed the e cacy of ceftazidimeavibactam (CAZ-AVI) and aztreonam-avibactam (ATM-AVI) against a selection of 76 S. maltophilia out of the 1179 strains isolated from the First A liated Hospital of Chongqing Medical University during 2011-2018. Methods: We investigated the antimicrobial resistance pro les of the 1179 S. maltophilia clinical isolates from the rst a liated hospital of Chongqing Medical Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A promising CZA association may be with fosfomycin, which has proved safe and effective in our case series and among VAPs due to S. maltophilia as well. A recent study by Moriceau et al seems to support this hypothesis and concludes that CZA for empirical treatments in severe or polymicrobial infections with S. maltophilia could be appropriate [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A promising CZA association may be with fosfomycin, which has proved safe and effective in our case series and among VAPs due to S. maltophilia as well. A recent study by Moriceau et al seems to support this hypothesis and concludes that CZA for empirical treatments in severe or polymicrobial infections with S. maltophilia could be appropriate [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data on ceftazidime-avibactam are more equivocal; Moriceau et. al and Lin et al describe decreases in minimum inhibitory concentration (MIC) with ceftazidime-avibactam compared to ceftazidime alone [51,52]. However, a significant subset of isolates remained resistant to the combination of ceftazidime-avibactam and additional studies reported only a minimal improvement to ceftazidime with the addition of avibactam [53].…”
Section: Novel Therapeuticsmentioning
confidence: 99%
“…It is worth noting that although CZA significantly decreased the MIC 50 and MIC 90 (p<0.001), there are no established breakpoints in the CLSI/EUCAST guidelines [ 28 ]. In a previous study by Moriceau et al, CZA demonstrated superior results compared to CAZ alone in terms of the proportion of susceptible isolates (66.7% vs. 38.9%, p<0.01) and MIC50 (2 μg/mL vs. 12 μg/mL, p<0.05) [ 29 ]. However, this option still appears appealing and mandates additional scrutiny and assessment.…”
Section: Discussionmentioning
confidence: 99%